The Anthropology of Fear of God Based on Allameh Tabatabai's Perspective: A Psychological Approach - mahmood khaliliyan shalamzari (Comparative Theology)
The difference in researchers’ attitudes towards human nature is not only the background and foundation of describing and explaining personality traits but also a platform for identifying and introducing new emotional states in humans. The purpose of this study is to identify the features of anthropology from Allameh Tabatabai’s point of view on the emergence of fear of God. The research method is qualitative. The qualitative analysis of the content of religious texts with a focus on description, explanation, and analysis has been used. The findings of the research showed that fear of God is a normal issue. In addition, fear of God has two types, fear in balance with hope and fear of divine position. Moreover, the phenomenon of fear of God is based on four characteristics in humans: 1) purposefulness, 2) the existential characteristics of man, 3) man with the motivation to avoid harm, and 4) the levels of man's knowledge of monotheism. The results showed that the origin of fear of God is not only external natural factors (such as lightning); rather, it is dependent on some characteristics of the disabled nature of the human being, the principle of orientation, and the lack of independence of an individual. Keywords: Fear of God, Purposefulness of Man, Existential Weakness, Motivation to Avoid Harm, Allameh Tabatabai. IntroductionIn psychology, fear is an avoidance reaction combined with the motivation of protection. Some psychologists (e.g. Freud, 1983) and philosophers (e.g. Russell, 1970) believe that external natural factors (such as thunder and lightning) are the main cause of fear in humans. They introduce fear as a factor in turning to God. On the contrary, in Allameh Tabatabai’s view, the origin of fear is within man. Man is the effect of God and God, as a true being, is the cause of the causes of other beings.Since the type of philosophical attitude towards human quiddity is the basis for explaining human personality and psychological states (Parvin and John, 2002), considering the difference in the views of Allameh Tabatabai and some Western psychologists and thinkers regarding the origin of fear (the inner essence of man or external natural factors), as well as the difference in the ontological system of Allameh in the analysis of the phenomenon of fear (the real God versus the God created by the mind), the purpose of this study is to explain the anthropology of fear of God based on Allameh Tabatabai's point of view. The meaning of fear of God is a person's concern about the threat of the goal, which strengthens the motivation of the person to achieve the goal and prevents him from committing and being close to the source of the threat (Khaliliyan Shalmazari et al., 2018). Therefore, this study seeks to answer the following research question:RQ1: In Allameh Tabatabai's view, which human characteristics are the origin of fear of God? Materials and MethodsThe research method is qualitative with the aim of investigating the anthropological features of fear of God from Allameh Tabatabai's viewpoint. For this purpose, the method of qualitative content analysis of religious texts, focusing on description, explanation, and analysis was used. Based on this, first, the divisions of fear of God were presented from Allameh Tabatabai’s viewpoint. In addition, deeper explanations and analyses of the text were made, focusing on the direction of discovering anthropological features. Then, by identifying the materials related to the anthropology of fear of God, more explanations were presented so that the features of his anthropology can be discovered and analyzed through their connection with the phenomenon of fear of God in humans. Research FindingsDivisions of Fear from the Perspective of Allameh TabatabaeiIn Allameh Tabatabai’s perspective, fear is divided into two types: jobn fear [abnormal and morbid fear] and hazm fear [normal and non-morbid fear] (Tabatabaei, 1995, p. 322-323). According to Allameh Tabatabai, absolute fear is not a morbid emotion; rather, it is considered an illness when it leads to the loss of nafs [weakness of will] and has three characteristics: 1) creating a state of confusion in a person, 2) moaning (alfaza), and 3) decreasing the ability to deal with the source of fear (Tabatabai, 1995, p. 321).Anthropological characteristics of fear of GodIn Allama Tabatabaei’s thought, the emergence of fear of God in humans is based on four characteristics: 1) purposefulness, 2) existential characteristics of humans (dependency and connectedness of humans), 3) motivated human beings to repel harm, and 4) levels of human knowledge of monotheism. Discussion of Results and ConclusionsTo Allameh Tabatabai, a human is not only a needy being but also a purposeful being. The analysis of behaviors and emotional traits in the thought of Tabatabai is based on the principle of directionality. Although this finding is in line with the positivist psychology perspective on meaning and purpose; however, the focus on transcendental goals versus individual goals is the distinguishing aspect of Allameh Tabatabai’s view. In the phenomenon of fear of God, attaining divine proximity and the benefits of the afterlife is a goal that directs all behaviors towards itself, which is beyond individual goals and basic needs in psychology.The understanding of poverty and need arises from the weakness of human existence in the face of the Creator and the cause of existence reminds us of the dependence and continuity of humans in connection to God. Based on this, unlike Freud and Russell, the origin of fear of God is not only external natural factors, it is the characteristic of human dependence and connection with God.